Penegakan Hukum Oleh Pos Lintas Batas Bagi Para Pelintas di Wilayah Perbatasan Papua dan Papua New Guinea - Novana Veronika Julenta Kareth (Balobe Law Journal, 2022)
Introduction: The urgency to organize the border between Indonesia and Papua New Guinea and border crossers is based on historical reasons that are more complex than the arrangement of Indonesia's borders with other countries.Purposes of the Research: To overcome these problems, the author proposes the idea of an integrated border management.Methods of the Research: This research uses sociological juridical method with the research location in Jayapura City.Results of the Research: The results of the study show that the border governance policies tend to ignore the cultural identity variable, which then encourages the use of cultural identity to challenge the state's version of dominant conceptions and policies in border governance. This is indicated by the phenomenon of "rat trails" and other cross-border interaction networks that are illegal by the state. Cultural approach in border governance policy is the principle that animates security policy, political policy, and economic policy in border governance. The practical consequence of this study is that border governance must move away from the domination of the economic security approach to an integrated approach.